Peran Sekuritisasi Sebagai Pendanaan Ekspansi Kredit Pemilikan Rumah Pada Bank BTN - Dede Hikmat Maulana; Hari Gursida; Yohanes Indrayono (Owner : Riset dan Jurnal Akuntansi, 2025)
Banks as intermediary institutions collect funds from the public in the form of and provide credit, one of which is Home Ownership Credit/KPR. However, there is a risk of a mismatch between funding and bank financing. KPR credit which has a long term is not comparable to funding sources from bank customer deposits which have a tenor of less than 1 year. Bank BTN as a bank that focuses on housing financing continues to pursue mortgage credit growth, one of which is by means of mortgage securitization. KPR securitization as a relatively cheap source of long-term funding is one of Bank BTN's ways of expanding KPR credit. The aim of this research is to determine the impact of securitization on the financial performance and company performance of Bank BTN.  This research is expected to provide an understanding regarding KPR securitization and the development of KPR credit in Indonesia, especially KPR securitization carried out by Bank BTN in the period 2018 to 2023. The analytical method used in this research is qualitative descriptive analysis. The data used in this research uses secondary data sources, including publications of company financial reports, government policies and regulator reports. Data collection techniques in this research used documentation, observation and interview techniques. The research results show that although KPR securitization has a positive impact on Bank BTN's liquidity and is used as an alternative source of financing for KPR expansion, it does not have a significant impact on shareholder profits.